Re-examination of the relationship between marine virus and microbial cell abundances - Wigington, Charles H.; Sonderegger, Derek; Brussaard, Corina P. D.; Buchan, Alison; Finke, Jan F.; Fuhrman, Jed A.; Lennon, Jay T.; Middelboe, Mathias; Suttle, Curtis A.; Stock, Charles; Wilson, William H.; Wommack, K. Eric; et al. (Nature microbiology, 2016)
Marine viruses are critical drivers of ocean biogeochemistry, and their abundances vary spatiotemporally in the global oceans, with upper estimates exceeding 10 8 per ml. Over many years, a consensus has emerged that virus abundances are typically tenfold higher than microbial cell abundances. However, the true explanatory power of a linear relationship and its robustness across diverse ocean environments is unclear. Here, we compile 5,508 microbial cell and virus abundance estimates from 22 distinct marine surveys and find substantial variation in the virus-to-microbial cell ratio, in which a 10:1 model has either limited or no explanatory power. Instead, virus abundances are better described as nonlinear, power-law functions of microbial cell abundances. The fitted scaling exponents are typically less than 1, implying that the virus-to-microbial cell ratio decreases with microbial cell density, rather than remaining fixed. The observed scaling also implies that viral effect sizes derived from ‘representative’ abundances require substantial refinement to be extrapolated to regional or global scales. Analysis of microbial cell and virus abundance estimates from 25 distinct marine surveys reveals that virus-to-microbial cell ratio decreases with microbial cell density, questioning the idea that viral abundance is always 10-fold higher.